2022
DOI: 10.1002/jmv.27947
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index: Is it associated with the prognosis of Crimean Congo hemorrhagic fever

Abstract: Introduction The prognostic nutritional index (PNI) is calculated using total serum lymphocyte counts and albumin levels. We aimed to analyze the role of PNI in predicting intensive care unit (ICU) referral and mortality in patients with Crimean Congo hemorrhagic fever (CCHF). Materials and Methods Our target population was adult (age >18) patients who presented between March 2015 and October 2021 within 5 days of symptom emergence and were diagnosed with CCHF. The predictive value of PNI was analyzed by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In our study, although there was no statistical difference between the amputee and non-amputee groups, the lymphocyte count was lower in the amputee group. Similar to our study, in studies evaluating the relationship between PNI and mortality in infective endocarditis and Crimean-Congo hemorrhagic fever, PNI was found to be significant, although there was no significant difference in lymphocyte count between the groups [8,21]. In the PNI formula, lower lymphocyte counts contribute to a lower PNI score, indicating potential immune system compromise.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, although there was no statistical difference between the amputee and non-amputee groups, the lymphocyte count was lower in the amputee group. Similar to our study, in studies evaluating the relationship between PNI and mortality in infective endocarditis and Crimean-Congo hemorrhagic fever, PNI was found to be significant, although there was no significant difference in lymphocyte count between the groups [8,21]. In the PNI formula, lower lymphocyte counts contribute to a lower PNI score, indicating potential immune system compromise.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous study, PNI was associated with mortality in COVID-19 infection [ 17 ]. In another study, a decrease in PNI was found to be associated with the exitus rate in Crimean-Congo hemorrhagic fever [ 18 ]. This study investigated the relationship between PNI and mortality in Gram-negative bacterial infections, showing a negative correlation similar to viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the PNI was used to assess preoperative nutritional status, surgical risk and postoperative complications in surgical patients [ 11 ]. However, a lower PNI was also reported to be associated with an increased risk of death in several conditions, including severe stroke [ 12 ], diabetic foot ulcers [ 13 ], Crimean-Congo hemorrhagic fever [ 14 ], heart failure [ 15 ] and CKD in elderly patients [ 16 ]. However, there is currently no evidence that the PNI is associated with all-cause mortality in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%